Implikasi Gadget Addiction terhadap Distraksi Ibadah Muslim Milenial di Kraksaan Jawa Timur - Muhammad Rizky Maulana; Nasrulloh (Al-Kindi, 2026)
This study investigates the influence of gadget addiction on worship distraction among Muslim millennials in Kraksaan, East Java, using a phenomenological qualitative approach combined with thematic analysis of hadith. It focuses on how intensive gadget use shapes mechanisms of distraction before, during, and after worship. Data were collected through in-depth interviews with 12 informants aged 18–30, participatory observations in several local mosques, and documentation of smartphone use immediately before and after prayer. Thematic analysis identifies three core patterns of distraction: compulsive checking behaviour, notification-driven interruptions, and cognitive residue from digital activities that carries over into worship. The findings indicate that gadget addiction affects not only outward behaviour but also diminishes spiritual presence, emotional stability, and the experience of khusyu’. By integrating empirical data with prophetic traditions on attentiveness in prayer, the study argues that digital distraction constitutes a contemporary form of “theft of devotion” analogous to the prohibition of turning away in prayer. This research contributes to the developing dialogue between hadith studies and digital psychology within the lived religiosity of Indonesian Muslim youth.